Faktor-Faktor Yang Menghambat Perawat Dalam Pengisian Logbook Kompetensi Di Rumah Sakit - Komsiyah Komsiyah; Suhartono Suhartono; Muhamad Rofi'i (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2018)
Background: The logbook by the Nursing Committee is one of the methods used to ensure that nurses are competent to carry out the clinical authority given to them. The use of the nurse logbook is proven useful as a monitoring tool and evaluation of the clinical competencies implementation and nurses' accountability tools for the clinical assignments given to them. Objective: To identify the completeness of nurses' competency logbook documents at the Hospital. Method: This study used mixed methods, which is a method that combines quantitative and qualitative approaches with a sequential explanatory model, with 136 respondents in the first stage by observing 136 nurses log book, and in the second stage conducting in-depth interviews involving 9 main participants and 6 triangulation participants to find out the inhibiting factors for implementing the nurses' competency logbook. Results: From 136 log book of administrators nurses obtain 13 complete logbook (9.5%), 41 (30.1%) logbook completeness is sufficient, and 82 (60.3%) logbook completeness is less. The results of the In-depth Interview obtain 8 themes, namely the function of the logbook, the completeness of the logbook documentation, the timing of filling, the filling factor, the supporting / driving factors of the filling, and the impact of not carrying out the logbook filling on time. Conclusion: The need for re-socialization to all nurses in order to improve understanding of the correct logbook method, the need to increase nurse motivation through gradual and continuous supervision and the need to establish clear rewards related to the implementation of filling out the nurse logbook.